Research on the Folding Patterns and Deployment Dynamics of Inflatable Capsule Structures - Hong,Yi-hong (2018)
ABSTRACT: The folding patterns and deployment dynamic characteristics of conical inflatable capsule structures were investigated. A six-fold-line method of packing a conical shell surface was designed. The fold-line layouts and relation formulas of the fold angles were determined. The folded state of the inflatable capsule structure was parametrically modeled; then, the deployment dynamic analysis model was established using ANSYS/LS-DYNA software. The dynamic characteristics of the inflatable capsule structure in orbit were numerically simulated. Thus, the deployment configurations and the time history curves of the dynamic characteristics were obtained. The results verified the feasibility of the fold pattern and the deployment dynamic analysis model. The influences of the residual gases from the packing process on the subsequent deployment process were investigated. The results indicated that a small amount of residual gas can lead to structures that cannot deploy smoothly, and two methods were presented to avoid this challenge. These works provide technical support for the structural designs of this type of inflatable capsule structure.